Design and fabrication of functional hydrogels with specific surface wettability - Wang, Shaohua; Yu, Peng; Li, Xinjin; Zhao, Zengdian; Dong, Yunhui; Li, Xiangye (Colloid and interface science communications, 2023)
Hydrogels have drawn widespread attentions in various fields for their superior properties, for example, high water content, transparency, good biocompatibility, variable mechanical strength and facile preparation. Surface properties of hydrogels, especially surface wettability, exhibit significant influences on their applications. In recent years, few strategies have been developed to tailor the surface wettability of hydrogels. It is meaningful to summarize the various reports published over the years, in which the importance of both chemistry and topography is described in terms of the surface wettability of hydrogels. This review will first summarize the basic theory of wettability, and then outline the strategies to modulate the surface wettability of hydrogels. Finally, current problems and challenges on tailoring the surface wettability of hydrogels will also be discussed. This review is supposed to be appealing to scientists interested in functional hydrogels and other novel engineered materials. [Display omitted] •Strategies to modulate the surface wettability of hydrogels is reviewed.•Importance of both chemistry and topography in imparting and modulating the surface wettability of hydrogels is discussed.•Current problems and challenges in modulating the surface wettability of hydrogels are discussed.